2004
DOI: 10.1258/0969141042467430
|View full text |Cite
|
Sign up to set email alerts
|

International comparison of performance measures for screening mammography: can it be done?

Abstract: Objective: Published screening mammography performance measures vary across countries. An international study was undertaken to assess the comparability of two performance measures: the recall rate and positive predictive value (PPV). These measures were selected because they do not require identification of all cancers in the screening population, which is not always possible. Setting:The screening mammography programs or data registries in 25 member countries of the International Breast Cancer Screening Netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
72
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 37 publications
4
72
2
2
Order By: Relevance
“…21,32 In contrast this research showed lower recall rates in the 51 to 55 years age group. Moreover, results revealed that younger women were more likely to have a negative diagnosis after the initial mammogram, and older women were more likely to be recalled.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…21,32 In contrast this research showed lower recall rates in the 51 to 55 years age group. Moreover, results revealed that younger women were more likely to have a negative diagnosis after the initial mammogram, and older women were more likely to be recalled.…”
Section: Discussioncontrasting
confidence: 76%
“…4 Previous research states that recall rates were influenced by several factors including training and experience of radiologists, image quality, the volume of mammograms interpreted and the age of screened women. 19,20,21 Early Recall Rate ER was found to be associated with a low predictive value for malignancy and thus every effort should be made to obtain a definitive diagnosis at initial assessment. 4,22,23,24 Additionally, a study analysing 110 women who were recalled early, revealed that 3.6% had invasive cancer, 0.9% had DCIS, while 84% had benign findings.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Since demonstration of the efficacy of mammographic screening in randomised trials, many developed countries have initiated mammography screening programmes [1]. It has been observed, both in the trials and the screening programmes, that survival is much better in women with screen-detected cancers than in those with tumours detected symptomatically [2][3][4].…”
Section: Introductionmentioning
confidence: 99%